2017
DOI: 10.1016/j.coal.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The Miocene coal seams in the Soma Basin (W. Turkey): Insights from coal petrography, mineralogy and geochemistry

Abstract: The Soma Basin hosts three coal seams (kM2, kM3 and kP1) and several altered tuff layers within the Miocene sequences. This study focuses on the determination of coal petrography, Rock-Eval pyrolysis, mineralogy and elemental contents of the three coal seams from Eynez, Işıklar and Deniş sectors in the basin, and to identify the mineralogy of altered tuff layers within * Corresponding author, **visiting scholar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 103 publications
1
49
0
Order By: Relevance
“…Several studies have reported that the sulfur origin of coals containing medium to high sulfur content could be derived from sulfate-and sulfide-rich source rocks via uplift and erosion and later transported to the mire through surface-and groundwater during peat growth in continental basins [85][86][87]. In addition, a high total sulfur content and an abundance of syngenetic pyrite crystals were also reported in coal seams within continental basins where palaeomires were fed by sulfate-rich groundwater [18,20,57,[87][88][89][90]. Furthermore, leached waters from tuff layers and volcanic rocks in adjacent areas, and S-rich epigenetic hydrothermal solutions into coal seams, could elevate the sulfur contents of coals [19,91,92].…”
Section: Interpretation Of Sulfur Enrichmentmentioning
confidence: 99%
“…Several studies have reported that the sulfur origin of coals containing medium to high sulfur content could be derived from sulfate-and sulfide-rich source rocks via uplift and erosion and later transported to the mire through surface-and groundwater during peat growth in continental basins [85][86][87]. In addition, a high total sulfur content and an abundance of syngenetic pyrite crystals were also reported in coal seams within continental basins where palaeomires were fed by sulfate-rich groundwater [18,20,57,[87][88][89][90]. Furthermore, leached waters from tuff layers and volcanic rocks in adjacent areas, and S-rich epigenetic hydrothermal solutions into coal seams, could elevate the sulfur contents of coals [19,91,92].…”
Section: Interpretation Of Sulfur Enrichmentmentioning
confidence: 99%
“…The framboidal pyrite was formed during peat development or in early diagenesis [31,64,[75][76][77]. Rickard et al [78] and Luther [79] suggested that the single crystal pyrite of framboids formed at low temperature (25 • C).…”
Section: Modes Of Occurrence Of Minerals In Coal and Carbonaceous Rocmentioning
confidence: 99%
“…Apatite occurred as a detrital form and as fine grains, both of which were coated by kaolinite ( Figure 14A,B). Detrital apatite was derived from terrestrial sources or volcanic ash [22,76,[80][81][82]. Albite occurred as euhedral crystals, and was distributed in the matrix of siderite ( Figure 14C).…”
Section: Modes Of Occurrence Of Minerals In Coal and Carbonaceous Rocmentioning
confidence: 99%
See 2 more Smart Citations